Economic and environmental sustainability of an AnMBR treating urban wastewater and organic fraction of municipal solid waste. (1st September 2016) - Pretel, R.; Moñino, P.; Robles, A.; Ruano, M.V.; Seco, A.; Ferrer, J.
Abstract: The objective of this study was to evaluate the economic and environmental sustainability of a submerged anaerobic membrane bioreactor (AnMBR) treating urban wastewater (UWW) and organic fraction of municipal solid waste (OFMSW) at ambient temperature in mild/hot climates. To this aim, power requirements, energy recovery from methane (biogas methane and methane dissolved in the effluent), consumption of reagents for membrane cleaning, and sludge handling (polyelectrolyte and energy consumption) and disposal (farmland, landfilling and incineration) were evaluated within different operating scenarios. Results showed that, for the operating conditions considered in this study, AnMBR technology is likely to be a net energy producer, resulting in considerable cost savings (up to €0.023 per m 3 of treated water) when treating low-sulphate influent. Life cycle analysis (LCA) results revealed that operating at high sludge retention times (70 days) and treating UWW jointly with OFMSW enhances the overall environmental performance of AnMBR technology. Highlights: The sustainability of an AnMBR was evaluated when treating UWW and OFMSW. Reagent and energy consumption, methane recovery and sludge production were studied. Operating at high SRT and treating UWW and OFMSW enhanced AnMBR sustainability. The increase in membrane cleaning reagent cost may be offset by the energy produced. Important cost savings could be achieved, mostly when treating low-sulphate influent.